1986
DOI: 10.1111/j.1095-8649.1986.tb04933.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein and lipid levels on growth, body composition and utilization efficiencies of Arctic charr, Salvelinus alpinus L.

Abstract: Growth. body composition and feed utilization were evaluated for Arctic charr fed a control diet and nine practical diets formulated to contain three protein levels (34.44 or 54%) at each of three lipid levels (10, 15 or 20%). Fish were raised for 24 weeks at 12" C. Increasing either dietary protein and/or lipid resulted in improved weight gain, feed efficiency and energy retained. Protein efficiency ratio and protein retained were directly related to dietary lipid and inversely related to dietary protein. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
(10 reference statements)
5
15
0
Order By: Relevance
“…In the present study, BWG and SGR increased with increasing protein in the diet up to 44% CP. These parameters significantly improved as the dietary protein level increased up to an optimum level, beyond which they plateaued or slightly decreased, consistent with results reported for other species including Arctic char, Salvelinus alpinus (Tabacheck 1986); red drum, Sciaenops ocellatus (Jirsa et al 1997); and Florida pompano, Trachinotus carolinus Lazo et al (1998). In some species, when the protein requirement is exceeded, the growth rate remains constant or decreases (Jauncey 1982).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, BWG and SGR increased with increasing protein in the diet up to 44% CP. These parameters significantly improved as the dietary protein level increased up to an optimum level, beyond which they plateaued or slightly decreased, consistent with results reported for other species including Arctic char, Salvelinus alpinus (Tabacheck 1986); red drum, Sciaenops ocellatus (Jirsa et al 1997); and Florida pompano, Trachinotus carolinus Lazo et al (1998). In some species, when the protein requirement is exceeded, the growth rate remains constant or decreases (Jauncey 1982).…”
Section: Discussionsupporting
confidence: 86%
“…Tabachek (1986) reported similar findings while investigating the influence of dietary protein and lipid levels on growth, body composition and utilization efficiencies of Arctic charr, Salvelinus alpinus L. Statistics further showed that PER of T3 was significantly higher (p<0.05) than other treatments. The significant value of PER in this study was as a result of the level of fat in the diet.…”
Section: Resultssupporting
confidence: 56%
“…Our results indicate that young Arctic charr require between 340 and 392 g kg-' dietary DCP (equivalent to -370 to -420 g kg-' crude protein) for optimum growth irrespective of the statistical method applied (Table 5). These levels are within the requirement range of 350-45Og kg-' dietary crude protein suggested by Jobling & Wandsvik (1983a) but are lower than the 440-54Og kg-' dietary crude protein range reported by Tabachek (1986) for this species. These values consequently confirm and refine the requirements recommended by Jobling & Wandsvik (1983a), giving a slightly reduced upper estimate and a narrower range.…”
Section: Resultssupporting
confidence: 49%
“…These values consequently confirm and refine the requirements recommended by Jobling & Wandsvik (1983a), giving a slightly reduced upper estimate and a narrower range. Tabachek (1986) compared her results with those of Jobling & Wandsvik (1983a) and suggested that their diets were too low in protein and/or lipid to allow a true measure of Arctic charr protein requirements, because the highest protein level they used (440g kg-I) provided only 1 l o g kg-' lipid. She reported that a higher level of lipid (150 or 200 g kg-I) promoted greater weight gain in charr fed both 440 and 540g kg-' crude protein diets and attributed this to the sparing effect of the extra lipid, which improved the efficiency of protein use for growth, as previously reported by Takeuchi et al (1978) for rainbow trout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation